2020
DOI: 10.3390/genes11091003
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Inhibitory Effects of Lentogenic Newcastle Disease Virus on Cell Survival and Immune Function in Spleen of Commercial Layer Chicks

Abstract: As a major infectious disease in chickens, Newcastle disease virus (NDV) causes considerable economic losses in the poultry industry, especially in developing countries where there is limited access to effective vaccination. Therefore, enhancing resistance to the virus in commercial chickens through breeding is a promising way to promote poultry production. In this study, we investigated gene expression changes at 2 and 6 days post inoculation (dpi) at day 21 with a lentogenic NDV in a commercial egg-laying ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 68 publications
(98 reference statements)
2
11
2
Order By: Relevance
“…Our IPA analysis also indicated the downregulation of some shared immune pathways with other in vivo NDV infections 20 . IL-8 signalling has a vital role during infectious disease by regulation of chemotaxis and activation of neutrophils 53 .…”
Section: Ingenuity Pathway Analysis Of Differentially Expressed Genesmentioning
confidence: 56%
See 4 more Smart Citations
“…Our IPA analysis also indicated the downregulation of some shared immune pathways with other in vivo NDV infections 20 . IL-8 signalling has a vital role during infectious disease by regulation of chemotaxis and activation of neutrophils 53 .…”
Section: Ingenuity Pathway Analysis Of Differentially Expressed Genesmentioning
confidence: 56%
“…Zhang et al (2020) study has recently reported 31 pathways with consistent expression response to nonvirulent strains of NDV 20 . Comparison of predicted pathways in our study with impacted pathways by lentogenic NDVs, revealed 16 shared pathways (Table 4).…”
Section: Ingenuity Pathway Analysis Of Differentially Expressed Genesmentioning
confidence: 97%
See 3 more Smart Citations